Musical Chairs : A Novel - Poeppel, Amy (New York : Emily Bestler Books/Atria, 2020)
"A novel about modern family life with all of its discord and harmony"--
Keywords: Friendship -- Fiction; Musicians -- Fiction; Families -- Fiction; Domestic fiction